The fundamental considerations of the public debt - Petkovski, Vladimir; Djambaska, Elizabeta; Kostadinoska Miloseska, Snezana (Economic Development, Journal of the Institute of Economics – Skopje, 2017)
Recent financial and economic crises in 2010 produce serious negative consequences for the fiscal stability and economic sovereignty in the most of the countries in the world. The most intimidating are the increased public debts. The paper explains some of the fundamentals considerations of the public debt, with the focus on the determination and definition of the public debt. Especially important contribution of this paper is the elaboration of the methodology of calculation and estimation of the level and state of the public debt and distinguishing of the main differences among the applied methodology.
Keywords: Public debt, Methodology, EFF methodology, ESA 95 methodology, ESA 2010 methodology